Can Economics Become More Reflexive? Exploring the Potential of Mixed-Methods - Rao, Vijayendra (World Bank, Washington, DC, 2022)
This paper argues that Economics can learn from Cultural Anthropology and Qualitative Sociology by drawing on a judicious mix of qualitative and quantitative methods to become more “reflexive.” It argues that reflexivity, which helps reduce the distance between researchers and the subjects of their research, has four key elements: cognitive empathy, the analysis of narratives (potentially enhanced by machine learning), understanding process, and participation (involving respondents in research). The paper provides an impressionistic and non-comprehensive review of mixed-methods relevant to development economics and discrimination to illustrate these points.